2018
DOI: 10.12659/msm.909800
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Attenuates Atrial Remodeling by Interfering with MicroRNA-21 and Downstream Phosphatase and Tensin Homolog (PTEN)/Phosphoinositide 3-Kinase (PI3K) Signaling Pathway

Abstract: BackgroundAtrial remodeling especially in the form of fibrosis is the most important substrate of atrial fibrillation (AF). The aim of this study was to investigate the effects of doxycycline on chronic intermittent hypoxia (CIH)-induced atrial remodeling and the pathophysiological mechanisms underlying such changes.Material/MethodsA total of 30 Sprague-Dawley rats were randomized into 3 groups: Control group, CIH group, and CIH with doxycycline treatment group. CIH rats were subjected to CIH 6 h/d for 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…Animal experiments showed that CIH was an important mediator of enhanced atrial vulnerability and susceptibility to AF. 19 Goudis and Ketikoglou 20 described that obstructive sleep apnea was associated with AF, which may implicate the pathophysiological mechanisms of AF. In addition, Zhang et al 21 showed that the percentage of the atrial collagen fraction in the CIH group was significantly increased compared with the values recorded in the control and intervention groups.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments showed that CIH was an important mediator of enhanced atrial vulnerability and susceptibility to AF. 19 Goudis and Ketikoglou 20 described that obstructive sleep apnea was associated with AF, which may implicate the pathophysiological mechanisms of AF. In addition, Zhang et al 21 showed that the percentage of the atrial collagen fraction in the CIH group was significantly increased compared with the values recorded in the control and intervention groups.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from electrical and structural remodeling associated to AF, other miRNAs are involved in AF targeting related pathways, i.e., miR-21 modulates Phosphatase and Tensin Homolog ( PTEN )/Phosphoinositide 3-kinase ( PI3K ) signaling pathway, signal transducer of transcription 3 ( STAT3 ) and Smad7 promoting atrial fibrosis; miR-31 begets arrhythmia by depleting dystrophin and neuronal nitric oxide synthase ( nNOS ); miR-34a is upregulated in AF patients having an important role in the early electrophysiological changes and development of AF via regulation of the expression of Ankyrin-B ( ANK 2 ); and finally, miR-199a down-regulation induces Sirtuin 1 ( SIRT-1 ), a cardio-protective protein, as a compensatory mechanism to inhibit the process of oxidative stress which contributes to the pathogenesis of AF [ 171 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Epigenetics Of Atrial Fibrillationmentioning
confidence: 99%
“…We then went on to explore the molecular mechanisms underlying such changes. Since miR‐21 plays a crucial role in cardiac fibrosis by affecting ERK and PI3K pathway, we tested the hypothesis that tolvaptan may similarly act via miR‐21/ERK and miR‐21/PI3K pathways for attenuating atrial remodeling. Indeed, our results indicated that CIH induced higher expression levels of miR‐21 and activation of ERK pathway, whereas PI3K/AKT pathway was inhibited in CIH rats.…”
Section: Discussionmentioning
confidence: 99%